Baby signing time! Vol. 1, It's baby signing time [videorecording (DVD)] - Babcock, Travis; Coleman, Rachel; Azevedo Brown, Emilie de (Two Little Hands Productions, 2005)
Teaches children how to sign what they want long before they can speak, with songs and activities that are both easy and fun. Encourages signing, speaking, dancing, and more.